Artemisinin inhibits breast cancer‐induced osteolysis by inhibiting osteoclast formation and breast cancer cell proliferation. Issue 8 (7th December 2018) - Li, Jia; Feng, Wenyu; Lu, Huiping; Wei, Yan; Ma, Shiting; Wei, Linfeng; Liu, Qian; Zhao, Jinmin; Wei, Qingjun; Yao, Jun
Abstract: In addition to being used to treat malaria, artemisinin (Art) can be used as an anti‐inflammatory and antitumor agent. In this study, we evaluated the effects of Art on osteoclast formation and activation and on the development of breast cancer cells in bone. To evaluate the effect of Art on osteoclast differentiation in vitro, we treated bone marrow‐derived macrophages (BMMs) with various concentrations of Art and evaluated the expression of genes and proteins involved in osteoclast formation. We also performed cell counting kit‐8 assays to evaluate the toxicity of Art in BMMs and MDA‐MB‐231 cells. We also performed Transwell assays, wound‐healing assays, colony formation assays, and cell apoptosis assays to evaluate the effect of Art in MDA‐MB‐231 cells. We also evaluated the effect of Art in an in vivo osteoclast bone resorption assay using a nude mouse model. We demonstrated that Art inhibits the differentiation and establishment of osteoclasts even though Art is not toxic to osteoclasts. In addition, Art reduced expression of genes involved in osteoclast formation and inhibited osteoclast bone resorption in a concentration‐dependent manner. Based on our data, we believe that Art can inhibit proliferation of breast cancer cells by activating apoptosis pathways, and inhibit osteoclast formation and differentiation by inhibiting activation of cathepsin K, ATPase H+ transporting V0 subunit D2, nuclear factor of activated T cells 1, calcitonin receptor, and tartrate‐resistant acid phosphatase and by inhibiting nuclear factor‐κB activation. Abstract : Art can inhibit proliferation of breast cancer cells by activating apoptosis pathways, and inhibit osteoclast formation and differentiation by inhibiting activation of cathepsin K, ATPase H+ transporting V0 subunit D2, nuclear factor of activated T cells 1, calcitonin receptor, and tartrate‐resistant acid phosphatase and by inhibiting nuclear factor‐κB activation.